2014
DOI: 10.1038/srep04834
|View full text |Cite
|
Sign up to set email alerts
|

Thermal-triggerd Proteinquake Leads to Disassembly of DegP Hexamer as an Imperative Activation Step

Abstract: The Escherichia coli DegP has been reported to function both as molecular chaperone and protease for the quality control of outer membrane protein biogenesis. Activation of the inactive DegP hexamers was believed to occur via their disassembly into trimeric units and subsequent reassembly into larger oligomers (12-mers and 24-mers). Here, we analyzed the thermal stability and the unfolding dynamics of the different secondary structure components of the DegP hexamers using Fourier transform infrared spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…In its protease-inactive state DegP forms a homohexameric complex 11 , which upon activation is able to re-arrange into dodecameric or 24-meric cage-like forms, suggested to encapsulate substrate proteins before proteolytic cleavage [12][13][14] . The common building block of the different cage-like structures is a DegP trimer, thus DegP is assumed to undergo large structural transitions from its hexameric resting state via a trimeric state towards the higher oligomeric states 15,16 . This structural transition itself is supposed to be mediated by modulations of the PDZ1-PDZ2 interaction 17 .…”
Section: Introduction (~3786/4000-4500 Main)mentioning
confidence: 99%
“…In its protease-inactive state DegP forms a homohexameric complex 11 , which upon activation is able to re-arrange into dodecameric or 24-meric cage-like forms, suggested to encapsulate substrate proteins before proteolytic cleavage [12][13][14] . The common building block of the different cage-like structures is a DegP trimer, thus DegP is assumed to undergo large structural transitions from its hexameric resting state via a trimeric state towards the higher oligomeric states 15,16 . This structural transition itself is supposed to be mediated by modulations of the PDZ1-PDZ2 interaction 17 .…”
Section: Introduction (~3786/4000-4500 Main)mentioning
confidence: 99%
“…The initial ultrafast protein response to the breaking of the bond between the ligand and the protein has been described as a quake-like motion of Mb, since the propagation of the strain released upon photoexcitation through the protein is similar to the propagation of acoustic waves during an earthquake 21 . Such ‘proteinquake’ model has been used to describe the structural dynamics of other haem 22 and non-haem proteins 23 24 25 . The analysis of the elastic response of the protein to the active site rearrangement is complicated by the simultaneous dissipation of the excess energy that is deposited by the photolysis pulse on the haem chromophore.…”
mentioning
confidence: 99%
“…Using Fourier transform-infrared spectroscopy and temperature-jump nanosecond time-resolved IR difference absorbance spectroscopy, we recently observed that the inactive DegP hexamers start to dissociate into trimers even at room temperature (25 8C) (20), allowing them to be converted to active large oligomers of 12 or 24 subunits (18,21). Our observations (20) also supported the claims of Kim et al (13) that the temperature-dependent effect observed for DegP protease activity was caused by a more extensive unfolding of the substrate proteins at a higher temperature, allowing them to better enter the central cavity of the active cage-like oligomeric DegP protein before effective cleavage can occur (18,21).…”
Section: Degp Functions More Likely As a Protease Rather Than A Chapementioning
confidence: 99%